The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physreve.94.042606
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational properties of quasi-two-dimensional colloidal glasses with varying interparticle attraction

Abstract: We measure the vibrational modes and particle dynamics of quasi-two-dimensional colloidal glasses as a function of interparticle interaction strength. The interparticle attractions are controlled via a temperature-tunable depletion interaction. Specifically, the interparticle attraction energy is increased gradually from a very small value (nearly hard-sphere) to moderate strength (∼4k_{B}T), and the variation of colloidal particle dynamics and vibrations are concurrently probed. The particle dynamics slow mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The introduction of disorder has a dramatic impact on the properties of a colloidal assembly: structural disorder can affect, for example, the vibrational and optical properties of a colloidal material and, hence, for instance, its interactions with sound and light. ,,,,, Restricting the attention to optical properties, different types of light–matter interactions have been pointed out for ordered systems, completely disordered systems, and intermediate regimes . Such effects can be related not only to the interparticle distance, but also to the specific arrangements, which exhibit distinctive features and affect local and collective coupling effects. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of disorder has a dramatic impact on the properties of a colloidal assembly: structural disorder can affect, for example, the vibrational and optical properties of a colloidal material and, hence, for instance, its interactions with sound and light. ,,,,, Restricting the attention to optical properties, different types of light–matter interactions have been pointed out for ordered systems, completely disordered systems, and intermediate regimes . Such effects can be related not only to the interparticle distance, but also to the specific arrangements, which exhibit distinctive features and affect local and collective coupling effects. , …”
Section: Discussionmentioning
confidence: 99%
“…More common analysis tools based, for instance, on the pair correlation function and other related metrics are suitable to characterize ordered systems consisting of a periodic repetition of a given unit cell and to identify the transition from a crystalline regime to noncrystalline ones, but they fail to provide a quantitative morphological characterization in a more disordered regime based on the coexistence of different symmetries. For example, the inadequacy of the pair correlation function to highlight structural transitions in disordered binary colloidal assemblies has been pointed out in refs , . Other analysis approaches, such as those based on the computation of the fractal dimension, have been adopted for the identification of structural changes in more disordered systems, especially in case of more sparse structures consisting of fractal-like aggregates, , but they still do not provide clues to recognition and quantification of dominant symmetries concealed in an amorphous assembly and require care in the selection of the computation method and parameters .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, also amorphous binary colloidal assemblies have attracted the attention of scientists. The introduction of disorder has a dramatic impact on material properties and important implications, for instance, in the interactions of a colloidal material with light or sound [11,17,19,20,21,22,23]. Restricting the attention to optical properties, it has been observed that ordered systems interact with light via collective modes resulting in diffraction, while completely disordered systems are dominated by Mie resonances of individual particles and random scattering; in the intermediate regime, collective modes, Mie resonances and near field interactions between individual scatterers all play a role; the transition between the different optical behaviors has been observed in binary colloidal assemblies for variable particle composition [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential interest of binary colloidal assemblies in the regime of loss of hexagonal order in practical applications, the analysis of their morphology poses more challenges in comparison to ordered assemblies. In fact, traditional analysis tools (such as the pair correlation function), which prove to be successful for the analysis of ordered assemblies [4,24,25,26], provide little clue to a comprehensive and thorough description of the colloidal morphology and fail to deliver a quantitative characterization of the patterns generated in these more disordered assemblies [12,21]. For such more complex structures, more sophisticated analysis tools need to be devised.…”
Section: Introductionmentioning
confidence: 99%